Subsurface Interpretation for Groundwater Potential Mapping Using Electrical Resistivity Tomography (ERT) in Mon Ikeun Village, Aceh Besar, Indonesia - Latifa, Adila; Sugiyanto, Didik; Syukri, Muhammad (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
The Mon Ikeun Village area in Aceh Besar is experiencing a clean water crisis due to a prolonged drought, which has significantly impacted human needs and necessitates identifying alternative water sources. This study aims to determine groundwater potential in the area using the Electrical Resistivity Tomography method. Data acquisition was conducted along three survey lines, each 420 m long. The Wenner-Schlumberger configuration was employed, using 22 electrodes with a spacing of 20 m. Data processing was done using ResIPy software to generate 2D resistivity cross-sections representing the subsurface structure. The resistivity sections were interpreted by correlating them with regional geological data and secondary data from wells located near the study area. The results indicate that two different lithologies dominate the subsurface structure of the study area. The first is a conductive zone with resistivity values of ≤316.23 Ω.m, interpreted as alluvium composed of clay, sand, and gravel. The second is a resistive zone with resistivity values of ≥562.34 Ω.m, interpreted as bedrock composed of limestone. Based on the subsurface lithology, zones with groundwater potential are found in conductive areas with resistivity values ranging from 3.16 to 56.23 Ω.m, which are associated with water-saturated alluvial layers, particularly those dominated by clay and sand. From the 2D resistivity cross-sections analysis, line 3 shows the highest potential for groundwater exploration, with water-saturated layers occurring at both shallow and deeper depths, reaching up to 0–40 m. This study provides valuable information for water resource management in Mon Ikeun Village, especially in addressing future clean water shortages.